Successful Fidaxomicin Hospital Discharges of Adult Patients With Clostridioides difficile Infections Post–2021 Guidelines: Are Economic Barriers Finally Coming Down?. (31st December 2021) - Fang, Noah; Ha, David; Dong, Kimberly; Leung, Thomas; Lee, Sydney; Holubar, Marisa; Meng, Lina
Abstract: We reviewed Clostridioides difficile– positive patients discharged on fidaxomicin after local adoption of 2021 C. difficile infection (CDI) guidelines. From 14 June to 3 October 2021, 80% (12/15) had copayments of $0–$35 and 27% (4/15) required prior authorization. The 30-day CDI recurrence was 7%.